Math, asked by YãÃrYÜvî, 1 year ago

solve it plzzzzzzzzzzzzzzzzzzzzzzzz

Attachments:

Answers

Answered by siddhartharao77
2
Given :  \frac{8k + 3}{k+1} -  \frac{9k-1}{k+1} - 2 = 0

LCM = k+1

= > 8k + 3 - (9k - 1) - 2(k + 1) = 0

= > 8k + 3 - 9k + 1 - 2k - 2 = 0

= > -3k + 2 = 0

= > -3k = -2

= > k = 2/3.


Therefore the value of k = 2/3.


Hope this helps!

siddhartharao77: :-)
tiwaavi: well
siddhartharao77: Thanks Tiwaavi
Answered by Anonymous
2
Hi,

Please see the attached file !


Thanks
Attachments:

YãÃrYÜvî: hello
YãÃrYÜvî: thanks brother
Anonymous: Welocme :) Mark as brainliest answer.
tiwaavi: well !!
Anonymous: Thank you tiwaavi Bhaiya :-)
Similar questions